Different interactions driving the binding of soy proteins (7S/11S) and flavonoids (quercetin/rutin): Alterations in the conformational and functional properties of soy proteins. (1st December 2022) - Jia, Yijia; Yan, Xinyue; Huang, Yuyang; Zhu, Huaping; Qi, Baokun; Li, Yang
Highlights: Quercetin/rutin quenched 7S/11S statically and 11S showed higher affinity. Rutin showed higher binding affinity to 7S/11S via hydrophobic interactions. Quercetin bonded to 7S/11S via van der Waals and hydrogen bonding interactions. Quercetin/rutin altered secondary structures and surface hydrophobicity of 7S/11S. The flavonoids affected the thermal stability and antioxidant capacity of 7S/11S. Abstract: The purpose of this research was to comparatively investigate the interactions between bioactive flavonoids (quercetin and rutin) and two predominant soy proteins (β-conglycinin and glycinin), and the structural and functional properties of their complexes. The binding affinities of quercetin/rutin toward 7S/11S were structure-dependent, in that rutin had a higher binding affinity than that of quercetin, and 11S exhibited higher affinity toward quercetin/rutin than that of 7S. The interactions in the 7S/11S–quercetin complexes were driven by van der Waals forces and hydrogen-bonding interactions, whereas the 7S/11S–rutin complexes exhibited hydrophobic interactions. Binding to quercetin or rutin altered the secondary structures (decrease in the α-helix and random coil contents and increase in the β-sheet content), decreased the surface hydrophobicity and thermal stability, and enhanced the antioxidant capacity of 7S and 11S. These findings provide valuable information that can facilitate the design of custom-tailored protein–flavonoid macromolecules.